2021
DOI: 10.3390/pr9091584
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cellulose Characteristics on Pyrolysis Suitability

Abstract: Cellulose is the most abundant component of biomass and the one that requires the most activation energy (Ea) for pyrolysis. In this study, the dependence of Ea on the intrinsic cellulose characteristics, such as the degree of polymerization (DP), crystallinity, and crystal size, was studied in different cellulose samples, including samples from Eucalyptus globulus, Ulmus minor, Linun usitatissimum, Olea europaea, Robinia pseudoacacia, and Populus alba. Then, to describe the pyrolytic degradation of cellulose,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the crystallinity index (CI) and cross-linking of cellulose have an inuence on the thermal behavior of composites. [642][643][644] Sinha and Rout 645 reported that chemical surface modication increases the thermal stability of PFRCs. It was reported that the thermal resistance of JFRCs shows better stability than pure polymers and other bres.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…Previous studies have demonstrated that the crystallinity index (CI) and cross-linking of cellulose have an inuence on the thermal behavior of composites. [642][643][644] Sinha and Rout 645 reported that chemical surface modication increases the thermal stability of PFRCs. It was reported that the thermal resistance of JFRCs shows better stability than pure polymers and other bres.…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…The result of cellulose degradation is an increased proportion of low molecular weight fractions and a decrease in average DP and polydispersity (PD) [ 18 , 19 , 20 , 21 ]. Moreover, DP, as well as crystallinity and crystallite size, have an influence on the thermal stability of cellulose [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%